Factors Contributing to Business Failure and Eventual Exit among Selected Tutorial Service Centers - Crisologo, Ma Louise Gena D.; Sarreal, Emilina R.; Tanpoco, Manuel R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
ess failure and exit are concomitants of business discontinuance which must be extensively studied as businesses such as tutorial centers can experience unfavorable events. This paper investigated the internal (i.e., owner/founder orientations) and external (i.e., compliance with government policies) antecedents leading to business failure and the eventual exit in the shadow education industry in 2013, particularly of Philippine privately owned tutorial centers which are divided into non-registered and registered services. Using the multiple case study approach, empirical findings showed that business failure is primarily caused by internal factors specifically the owner/founder orientations, while non-compliance with government regulations is secondary. The owner/founder orientations were comprised of motivation, characteristics/behavior, skill managerial deficiencies, capabilities, and financial knowledge shortcomings. Non-registered tutorial centers asserted that only skill/managerial deficiencies and capabilities lead to failure while registered tutorial services perceived all as reasons for business failure. Not complying with government policies can affect more the registered tutorial services than the non-registered centers. Business exit was chosen by all the owners of tutorial centers as a viable option in case of business failure. Future studies can consider obtaining more participants and comprehensively investigating tutorial centers from different countries to enrich cross-country research in shadow education.